Development of a cost-effective high-throughput mid-density 5K genotyping assay for germplasm characterization and breeding in groundnut - Pandey, Manish K.; Sharma, Vinay; Khan, Aamir W.; Pushpesh, Joshi; Gangurde, Sunil S.; Bajaj, Prasad; Pasupuleti, Janila; Chitikineni, Annapurna; Bhat, Ramesh; Motagi, Babu N.; Sangh, Chandramohan; Radhakrishnan, Thankappan; et al. (Wiley, 2025)
Groundnut (Arachis hypogaea L.), also known as peanut, is an allotetraploid legume crop composed of two different progenitor sub-genomes. This crop is an important source for food, feed, and confectioneries. Leveraging translational genomics research has expedited the precision and speed in making selections of progenies in several crops through either marker-assisted selection or genomic selection, including groundnut. The availability of foundational genomic resources such as reference genomes for diploid progenitors and cultivated tetraploids, offered substantial opportunities for genomic interventions, including the development of genotyping assays. Here, a cost-effective and high-throughput genotyping assay has been developed with 5,081 single nucleotide polymorphisms (SNPs) referred to as “mid-density assay.” This multi-purpose assay includes 5,000 highly informative SNPs selected based on higher polymorphism information content (PIC) from our previously developed high-density “Axiom_Arachis” array containing 58,233 SNPs. Additionally 82 SNPs associated with five resilience and quality traits were included for marker-assisted selection. To test the utility of the mid-density genotyping (MDG) assay, 2,573 genotypes from distinct sets of breeding populations were genotyped with the 5,081 SNPs. PIC of the SNPs in the MDG ranged from 0.34 to 0.37 among diverse sets. The first three principal components collectively explained 82.08% of the variance among these genotypes. The mid-density assay demonstrated a proficient ability to distinguish between the genotypes, offering a high level of genome-wide nucleotide diversity. This assay holds promise for possible deployment in the identification of varietal seed mixtures, genetic purity within gene bank germplasms and seed systems, foreground and background selection in backcross breeding programs, genomic selection, and sparse trait mapping studies in groundnut.